Optimizing Santripreneur Development through Sharia-Based E-Commerce Startups and Tax Compliance in Modern Islamic Boarding Schools - Rahmawati; Putri Ayu Ramadhani; Muhammad Wahyuddin Abdullah; Supriadi; Nurwahida (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the optimization strategy for santripreneur development through the utilization of Sharia-based e-commerce startups and to examine the level of tax compliance within modern Islamic boarding schools. Employing a descriptive qualitative approach with a case study method, the research explores pesantren that have implemented digital entrepreneurship initiatives. The findings reveal that the application of Sharia-based e-commerce significantly enhances the economic independence of santri and expands the marketing network of pesantren products while promoting ethical and transparent business practices. However, low tax literacy among santri entrepreneurs remains a key challenge in achieving fiscal compliance. Integrating tax education and Sharia e-commerce training within the pesantren’s entrepreneurship curriculum is therefore crucial to establishing a sustainable santripreneur ecosystem that aligns with Islamic principles and national taxation laws. The study also highlights the strategic role of digitalization in transforming pesantren into centers of halal entrepreneurship and financial accountability. By combining religious, economic, and fiscal dimensions, this model contributes to the creation of responsible, innovative, and competitive santri entrepreneurs in the digital era. Future research is recommended to empirically validate this conceptual framework through field studies across diverse pesantren contexts.